Opisthorchosis of fishes in the West of Kazakhstan - R. S. Karmaliev; J. M. Kereev (Российский паразитологический журнал)
It is established high infection of fishes by Opisthorchis felineus and diseases of the population with opisthorchosis in the West of Kazakhstan.